2016
DOI: 10.1111/imm.12628
|View full text |Cite
|
Sign up to set email alerts
|

Rel B‐modified dendritic cells possess tolerogenic phenotype and functions on lupus splenic lymphocytes in vitro

Abstract: SummarySystemic lupus erythematosus (SLE) is an autoimmune disease that is characterized by high morbidity and mortality and its treatment remains challenging. Dendritic cells (DCs) have been shown to participate in the initiation and perpetuation of lupus pathogenesis and the DCs that can induce tolerogenicity appear as potential cell‐based therapy in this condition. In this study, we examined the in vitro tolerogenic properties of bone‐marrow derived DCs (BMDCs) in the murine lupus setting. We used lentivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…On the other hand, RELB is a subunit of NF-κB and takes part in the development of dendritic cells [ 49 ]. In the murine lupus model, Relb-modified dendritic cells decreased the interferon-γ expression [ 50 ]. ARNTL is a TF that forms a core component of the circadian clock.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, RELB is a subunit of NF-κB and takes part in the development of dendritic cells [ 49 ]. In the murine lupus model, Relb-modified dendritic cells decreased the interferon-γ expression [ 50 ]. ARNTL is a TF that forms a core component of the circadian clock.…”
Section: Discussionmentioning
confidence: 99%
“…RelB is potentially translocated into the nucleus and activated when signal-induced noncanonical NF-κB kinase NIK degradation occurs (Sun, 2011). Recent evidence has revealed that disordered RelB in different cell types is generally associated with various autoimmune and inflammatory conditions, including IgA nephropathy (Jin et al, 2012), rheumatoid arthritis (Pettit et al, 2000), EAE (Ginwala et al, 2017), systemic lupus erythematosus (Wu et al, 2016), and psoriasis (Barton et al, 2000). However, to date, it remains largely unclear how RelB and the upstream kinase NIK are negatively regulated in myeloid cells.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, RelB-silenced tolerogenic DCs are used to study autoimmune diseases, such as systemic lupus erythematosus and myasthenia gravis. Moreover, significant protective effects have been observed in disease conditions [177][178][179]. In a very recent research, Andreas and his team found that mice with RelB-deficient DCs are almost resistant to induction of the EAE model because of the accumulation of FoxP3+ Tregs and the reduction of pathogenic T cells [180].…”
Section: Dendritic Cellsmentioning
confidence: 99%